2023
DOI: 10.1021/acsami.3c00857
|View full text |Cite
|
Sign up to set email alerts
|

Operando Revealing the Crystal Phase Transformation and Electrocatalytic Activity Correlation of MnO2 toward Glycerol Electrooxidation

Abstract: In this work, we report for the first time a comprehensive operando investigation of the intricate correlation between dynamic phase evolution and glycerol electrooxidation reaction (GEOR) performance across three primary MnO 2 crystallographic phases (α-, β-, and γ-MnO 2 ). The results showed that all three electrocatalysts exhibited comparable selectivity toward three-carbon products (∼90%), but γ-MnO 2 exhibited superior performance, with a low onset potential of ∼1.45 V RHE , the highest current density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“… Three dominant peaks, v 1 to v 3 , can be identified in the range of 200–700 cm –1 (Figure d). To elaborate, the frequency range of v 1 (620 cm –1 to 650 cm –1 ) is linked to Mn–O stretching vibrations that are perpendicular to the sheet of MnO 6 octahedra and symmetric stretching of the Mn–O bond within the MnO 6 octahedra unit, while v 2 (570 and 590 cm –1 ) signifies the Mn–O stretching vibration occurring within the plane of MnO 6 octahedra. Compared to the previously reported Raman spectra of fine-crystalline MnO 2 , such as α-MnO 2 , γ-MnO 2 , and δ-MnO 2 , a significant blue shift of the v 2 band is observed in both Amo-MnO 2 and L-Cry-MnO 2 . This shift is attributed to the structural distortions in both samples, verifying their amorphous characteristics.…”
Section: Resultsmentioning
confidence: 99%
“… Three dominant peaks, v 1 to v 3 , can be identified in the range of 200–700 cm –1 (Figure d). To elaborate, the frequency range of v 1 (620 cm –1 to 650 cm –1 ) is linked to Mn–O stretching vibrations that are perpendicular to the sheet of MnO 6 octahedra and symmetric stretching of the Mn–O bond within the MnO 6 octahedra unit, while v 2 (570 and 590 cm –1 ) signifies the Mn–O stretching vibration occurring within the plane of MnO 6 octahedra. Compared to the previously reported Raman spectra of fine-crystalline MnO 2 , such as α-MnO 2 , γ-MnO 2 , and δ-MnO 2 , a significant blue shift of the v 2 band is observed in both Amo-MnO 2 and L-Cry-MnO 2 . This shift is attributed to the structural distortions in both samples, verifying their amorphous characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…γ-MnO 2 delivered a superior performance with a lower onset potential owing to the preferential adsorption of secondary –OH groups on the surface. 191 MnO 2 fabricated on carbon paper in acidic media showed an impressive stability of 865 h along with a lower onset potential of 1.36 V RHE (270 mV lower than that for the OER) and lower Tafel slope (243.1 mV dec −1 ). The in situ Raman and DFT studies revealed that glycerol addition enhanced the stability of MnO 2 , inhibiting its dissolution and lattice oxygen processes, which led to high stability of electrode and selective production of FA.…”
Section: Electrocatalytic Valorization Of Glycerolmentioning
confidence: 99%